2017
DOI: 10.1016/j.ejcb.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of cell cycle arrest and terminal differentiation in a maximally proliferative human epithelial tissue: Lessons from the human hair follicle matrix

Abstract: Human hair follicle (HF) growth and hair shaft formation require terminal differentiation-associated cell cycle arrest of highly proliferative matrix keratinocytes. However, the regulation of this complex event remains unknown. CIP/KIP family member proteins (p21, p27 and p57) regulate cell cycle progression/arrest, endoreplication, differentiation and apoptosis. Since they have not yet been adequately characterized in the human HF, we asked whether and where CIP/KIP proteins localise in the human hair matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 83 publications
1
56
0
Order By: Relevance
“…Paclitaxel promoted the extensive accumulation of irregular and shrunken nuclei that localised specifically to the most proliferative region of the hair matrix (Fig A; i.e. predominantly below the critical line of Auber; Purba et al , , 2017a). Docetaxel treatment (24 h) also promoted the formation of irregular nuclear bodies within the hair matrix, albeit not to the extent seen following paclitaxel treatment (Fig B–E).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Paclitaxel promoted the extensive accumulation of irregular and shrunken nuclei that localised specifically to the most proliferative region of the hair matrix (Fig A; i.e. predominantly below the critical line of Auber; Purba et al , , 2017a). Docetaxel treatment (24 h) also promoted the formation of irregular nuclear bodies within the hair matrix, albeit not to the extent seen following paclitaxel treatment (Fig B–E).…”
Section: Resultsmentioning
confidence: 97%
“…Goat anti‐Mouse/Rabbit Secondary Antibodies, Alexa Fluor 488/594 (Invitrogen, #A11001, #A11005 #A11008 #A11037) (1:200). See also supporting references (Purba et al , , ,b).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The selection of resveratrol to be associated with STX was based on its properties to reduce ROS and inflammation, described in alopecia . We showed that a pre‐treatment with resveratrol protected the hair matrix cells when exposed to a generator of ROS, which is of importance as the hair matrix cells are the key player to produce the hair shaft and must be preserved to guarantee the hair density. In this study, the results highlighted the property of resveratrol to protect the whole hair follicle in vitro , blocking the generation of ROS in the hair cells induced by H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analysis of EU incorporation within the matrix, pre-cortex, IRS and DP of the HF bulb [9,10] showed relative compartmental homogeneity in levels of RNA synthesis, as no significant differences in EU signal were seen between these cell populations (Figure 1CD). Supporting this, visualization of proliferation (Ki-67) [9,10] against EU incorporation revealed no distinguishable pattern of RNA synthesis that associated with either cell cycle activity or arrest in this compartment (Figure 1E).…”
mentioning
confidence: 98%